Catalyst free visible light induced cycloaddition as an avenue for polymer ligation. Issue 35 (23rd March 2016) - Lederhose, Paul; Wüst, Kilian N. R.; Barner-Kowollik, Christopher; Blinco, James P.
Abstract : The current study introduces a tetrazole species able to perform a rapid, visible light induced nitrile imine-mediated tetrazole-ene cycloaddition (NITEC). Abstract : The current study introduces a tetrazole species able to perform a rapid, visible light induced nitrile imine-mediated tetrazole-ene cycloaddition (NITEC). Full conversion of the tetrazole species under mild, catalyst free conditions is reported. Importantly, the visible light ligation technology is applied as a method for the modification and ligation of polymers featuring the rapid, clean and exclusive formation of the desired cycloadduct.